Modificación de la composición tisular y sensorial de la canal de cuyes parrilleros mediante restricción alimentaria en la fase de acabado - Meza-Rojas, Elmer (2025)
The effect of temporary feed restriction on tissue composition and sensory attributes of aroma and appearance of guinea pig carcasses was evaluated. Forty-eight weaned male and female guinea pigs, 12 ± 2 days old, with initial weights of 267.8 ± 18.8 g were selected. Treatments consisted of a temporary 50% reduction in feed supplementation relative to the control (unrestricted) during the final weeks of the finishing phase and for a period of 0, 7, 14, and 21 days. The carcasses of the slaughtered animals were lightly cooked, and the tissue components were manually separated. After cooking, half of the carcasses were placed on trays for hedonic evaluation by 50 habitual consumers of guinea pig meat. A randomized complete block design was used for tissue data, and the Friedman test was used to analyse sensory attributes. The 7- and 14-day restriction did not modify the proportion of muscle tissue, but significantly reduced the amount of adipose tissue, while day 21 resulted in a significant reduction in both components. The proportion of skin was not affected. The 14-day restriction improved the perception of aroma and appearance. It is concluded that a 50% reduction in the daily ration of a food supplement for a period of up to 14 days favourably modifies the ratio of muscle, fat, and bone tissue in the carcasses of guinea pigs, while sensory perception significantly improves on day 7 of restriction.